Real-time non-destructive characterization of epoxy resin curing kinetics and mechanical response for enhanced manufacturing quality control - Gonzalo Seisdedos; Edgar Viamontes; Eduardo Salazar; Cristian Pantea; Eric S. Davis; Tommy Rockward; Benjamin Boesl (Polymer Testing)
Controlling and monitoring the processing parameters during epoxy manufacturing is a challenging task and their variation impacts the curing process of the polymer and its final quality. To address this issue, destructive testing is typically performed for quality control and material characterization, which involves expensive lab-type equipment and instrument-specific sample preparation. Moreover, this type of testing cannot be taken in-field to perform an in-situ evaluation. This work presents a method to non-destructively evaluate the curing kinetics and viscoelastic properties of epoxy resin in real time due to variations in stoichiometry combining ultrasonics and Fourier Transform Infrared Spectroscopy. Samples with a different amine-to-epoxy ratio were manufactured and tested. Thermogravimetric analysis revealed that deviations from the recommended ratio promoted thermal degradation. Furthermore, changes in longitudinal sound speed were detected during the resin's curing process, resulting from variations in the polymer's chemical structure, and were correlated to the cure kinetics. The sound speeds of three baseline samples were determined during the curing process with an absolute error of ∼0.13 % while changing the amine content by ±40 % caused alterations in the curing process and changes in the final sound speeds of up to ∼3.6 %. The longitudinal and shear sound speeds were used to calculate the elastic properties of the material, including Young's modulus and Poisson's ratio. Finally, the curing kinetics were modeled using the Hill equation to better understand numerically the effect of varying stoichiometry in the curing process. This approach has the potential to non-destructively characterize the properties of polymers in both an in-field and manufacturing setting, aiding in the tailoring process and ensuring their reliability in demanding applications.